PERSISTENT GENITAL AROUSAL DISORDER INTERVENTION WITH MANUAL PHYSIOTHERAPY - A CASE STUDY - Sf, Mariyam Farzana; Ts, Veera Goudhaman; Ms, Pawan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
A 36-year-old female patient came with an bilateral lower extremity pain and altered sensation, physical evaluation and radiological finding are normal, and there was presence of myofascial trigger points in both lower extremities diagnosed as a myofascial pain syndrome (MPS) and had been treated for it. The failure of treatment for MPS is followed by reevaluation, and on subjective evaluation, her genital symptoms such as unresolving genital arousal, fullness, engorgement, and restless leg syndrome were revealed, and on the objective evaluation, there was an overactive pelvic floor muscles; with subjective and objective findings, the problem was diagnosed as persistent genital arousal disorder (PGAD), the problem causing pathoanatomic structure and pathomechanism was discovered and addressed with manual physiotherapy, and the patient got complete solution from the PGAD. The informed consent was obtained from the patient.